Aluminum-based eutectic electrolyte, preparation method thereof, and secondary aluminum ion battery

By using aluminum-based eutectic electrolytes, using aluminum salts and hydrogen bonding ligands to form eutectic solvents, and adding diluents, the problems of unrealized energy density and strong corrosiveness of existing aluminum-ion battery electrolytes are solved, and a more efficient solution is achieved. High conductivity, fluidity and safety.

CN115411356BActive Publication Date: 2025-01-21SHANGHAI JIAOTONG UNIV
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202211054329.7
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2022-08-29
Publication Date
2025-01-21
Estimated Expiration
2042-08-29

AI Technical Summary

Technical Problem

The existing aluminum ion battery electrolyte AlCl3/[EMIm]Cl has technical problems that the actual energy density cannot be achieved, and the strong corrosion resistance leads to limited battery service life and safety.

Method used

An aluminum-based eutectic electrolyte is used. The electrolyte is composed of aluminum salt, hydrogen bonding ligands and diluent. The eutectic solvent is formed by mixing the aluminum salt and hydrogen bonding ligands, and a diluent is added to reduce the viscosity and improve the conductivity. .

Benefits of technology

The conductivity and fluidity of the battery are improved, the interface resistance and corrosion are reduced, the service life of the battery is extended and safety is improved, and a higher reversible discharge capacity is achieved.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN115411356B_ABST
    Figure CN115411356B_ABST
Patent Text Reader

Abstract

The present invention provides an aluminum-based eutectic electrolyte, a preparation method thereof, and a secondary aluminum ion battery, and specifically relates to the field of electrochemical energy storage technology. The aluminum-based eutectic electrolyte comprises an aluminum salt, a hydrogen-bonding ligand, and a diluent; the viscosity is less than 40 mPa / s. In the aluminum-based eutectic electrolyte provided by the present invention, the aluminum salt and the hydrogen-bonding ligand are mixed to form a eutectic solvent, which improves the conductivity of the battery. The addition of the diluent reduces the viscosity of the eutectic solvent, improves the fluidity of the aluminum-based eutectic electrolyte, and increases the ion conduction speed; the reduced viscosity also increases the wettability of the eutectic solvent to the diaphragm, reduces the ion transmission path, is beneficial to the movement of aluminum ions between the positive and negative electrodes, and reduces the interface resistance of the aluminum ion battery. The aluminum-based eutectic electrolyte provided by the present invention is not easy to react with common metals, has low corrosiveness, and ensures the service life and safety of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of electrochemical energy storage, and in particular to an aluminum-based eutectic electrolyte, a preparation method thereof, and a secondary aluminum ion battery. Background Art

[0002] Aluminum ion batteries are considered to be a strong competitor in the field of new energy storage technology. The theoretical volumetric capacity of aluminum is as high as 8046mA·h / cm 3 The theoretical mass specific capacity is also 2980mA·h / g, which has great advantages compared with other metal ion battery systems. Moreover, the mainstream aluminum ion electrolyte is not flammable, which essentially solves the safety problem of the battery. At the same time, aluminum is the most abundant metal element in the earth's crust, with low cost, high safety and environmental friendliness. These advantages make aluminum ion batteries have broad application prospects in the field of energy storage.

[0003] So far, the commonly used electrolyte for aluminum ion batteries is AlCl3 / [EMIm]Cl ionic liquid. This ionic liquid can achieve efficient reversible deposition / stripping of aluminum and is the most commonly used electrolyte for aluminum ion batteries. However, the carrier ion in this ionic liquid is a monovalent compound: AlCl4 - and Al2Cl7 - , rather than trivalent Al 3+ , which means that aluminum-ion batteries based on Al 3+ The value of the high theoretical capacity of the three electron transfer reactions cannot be fully realized. Therefore, the actual energy density of aluminum ion batteries is still not achieved. In addition, AlCl3 / [EMIm]Cl ionic liquid has severe corrosiveness, and Al2Cl7 - and Cl - The ions can react with common metals such as aluminum, iron, nickel, titanium and tungsten, which not only shortens the service life of the Al anode in aluminum-ion batteries, but also severely limits the choice of battery current collectors and casings.

[0004] In view of this, the present invention is proposed. Summary of the invention

[0005] One of the purposes of the present invention is to provide an aluminum-based eutectic electrolyte to alleviate the technical problems in the prior art that AlCl3 / [EMIm]Cl ionic liquid is used as an aluminum ion battery electrolyte, resulting in a large difference between the actual capacity and density of the aluminum ion battery and the theoretical value, and is prone to corrosion as an aluminum ion battery electrolyte.

[0006] In order to achieve the above-mentioned purpose of the present invention, the following technical solutions are particularly adopted:

[0007] A first aspect of the present invention provides an aluminum-based eutectic electrolyte comprising an aluminum salt, a hydrogen-bonding ligand and a diluent.

[0008] Optionally, Al 3+ Concentration <5mol / L.

[0009] Preferably, the viscosity of the aluminum-based eutectic electrolyte is lower than 40 mPa / s.

[0010] Optionally, the molar ratio of the aluminum salt to the hydrogen bonding ligand is 1:1-15.

[0011] Preferably, the volume ratio of the total volume of the aluminum salt and the hydrogen bonding ligand to the volume of the diluent is 1:0.5-5.

[0012] Optionally, the aluminum salt includes at least one of aluminum chloride, aluminum chloride hexahydrate, aluminum trifluoromethanesulfonate, aluminum nitrate, aluminum nitrate nonahydrate, aluminum perchlorate, aluminum perchlorate nonahydrate, aluminum sulfate and aluminum sulfate 18hydrate.

[0013] Optionally, the hydrogen bonding ligand includes at least one of sulfone compounds, alcohol compounds, urea and its derivatives, piperidine compounds, nitrile compounds and amide compounds.

[0014] Preferably, the sulfone compound includes dimethyl sulfoxide and / or sulfolane.

[0015] Preferably, the alcohol compound includes at least one of ethylene glycol, polyethylene glycol-200, polyethylene glycol-400 and polyethylene glycol-600.

[0016] Preferably, the urea and its derivatives include at least one of urea, N-methylurea and ethylurea.

[0017] Preferably, the piperidine compound comprises tetramethylpiperidinyl oxide and / or 4-methoxy-tetramethylpiperidinyl oxide free radical.

[0018] Preferably, the nitrile compound comprises succinonitrile and / or acetonitrile.

[0019] Preferably, the amide compound includes at least one of thioacetamide, methylamide and acetamide.

[0020] Optionally, the diluent comprises a hydrofluoroether compound.

[0021] Preferably, the hydrofluoroether compound includes at least one of 2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl ethyl ether, 1,1,2,2-tetrafluoroethyl methyl ether and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0022] The second aspect of the present invention provides a method for preparing the aluminum-based eutectic electrolyte, wherein the aluminum salt and the hydrogen-bonding ligand are mixed evenly, heated and then cooled, and a diluent is added and mixed evenly to obtain the aluminum-based eutectic electrolyte.

[0023] Optionally, the heating temperature is 40°C-60°C.

[0024] Preferably, the heating time is 30 min-60 min.

[0025] Preferably, the method further comprises a stirring process after heating and cooling, and the stirring time is preferably 1 h to 6 h.

[0026] A third aspect of the present invention provides a secondary aluminum ion battery, comprising a positive electrode material, a negative electrode material and an electrolyte solution;

[0027] Wherein, the electrolyte solution is the aluminum-based eutectic electrolyte.

[0028] Optionally, the positive electrode material is Al 3+ Storage material, the negative electrode material is aluminum foil.

[0029] Preferably, the Al 3+ The storage material includes at least one of vanadium pentoxide, manganese dioxide, molybdenum disulfide, polyaniline, Prussian blue and graphite.

[0030] Preferably, the aluminum foil includes pure aluminum foil and / or Al—Mg—Sn alloy foil.

[0031] Preferably, the thickness of the aluminum foil is 1 μm-300 μm.

[0032] Compared with the prior art, the present invention has at least the following beneficial effects:

[0033] The aluminum-based eutectic electrolyte provided by the present invention is a eutectic solvent formed by mixing aluminum salt and hydrogen-bonding ligands, which is in a liquid state at room temperature. The eutectic solvent is entirely composed of ions, which improves the conductivity of the battery. The addition of a diluent reduces the viscosity of the eutectic solvent, improves the fluidity of the aluminum-based eutectic electrolyte, and increases the ion conduction speed; the reduced viscosity also increases the wettability of the eutectic solvent to the diaphragm, reduces the ion transmission path, is conducive to the shuttling of aluminum ions between the positive and negative electrodes, and reduces the interface resistance of the aluminum ion battery. The aluminum-based eutectic electrolyte provided by the present invention is not easy to react with common metals, has low corrosiveness, and ensures the service life and safety of the battery.

[0034] The method for preparing the aluminum-based eutectic electrolyte provided by the present invention has a simple process and a large processing capacity and is suitable for large-scale industrial production.

[0035] The secondary aluminum ion battery provided by the present invention uses an aluminum-based eutectic electrolyte, so that the reversible discharge capacity of the battery can reach 300 mAh g -1 The secondary aluminum ion battery has high specific capacity, good cycle stability, higher safety, and is suitable for large-scale promotion and use. BRIEF DESCRIPTION OF THE DRAWINGS

[0036] In order to more clearly illustrate the specific implementation methods of the present invention or the technical solutions in the prior art, the drawings required for use in the specific implementation methods or the description of the prior art will be briefly introduced below. Obviously, the drawings described below are some implementation methods of the present invention. For ordinary technicians in this field, other drawings can be obtained based on these drawings without paying creative work.

[0037] Figure 1 Line graph of concentration and viscosity data provided for Test Example 1;

[0038] Figure 2 The charge and discharge curve of the aluminum ion battery provided in Example 1;

[0039] Figure 3 The charge and discharge curve of the aluminum ion battery provided in Example 2;

[0040] Figure 4 The charge and discharge curve of the aluminum ion battery provided in Example 3;

[0041] Figure 5 The charge and discharge curve of the aluminum ion battery provided in Example 4;

[0042] Figure 6 The charge and discharge curve of the aluminum ion battery provided in Example 5;

[0043] Figure 7 The charge and discharge curve of the aluminum ion battery provided in Example 6;

[0044] Figure 8 This is the charge and discharge curve of the aluminum ion battery provided in Example 7. DETAILED DESCRIPTION

[0045] The embodiments of the present invention will be described in detail below in conjunction with the embodiments and examples, but those skilled in the art will understand that the following embodiments and examples are only used to illustrate the present invention and should not be considered to limit the scope of the present invention. Based on the embodiments in the present invention, all other embodiments obtained by ordinary technicians in this field without making creative work are within the scope of protection of the present invention.

[0046] A first aspect of the present invention provides an aluminum-based eutectic electrolyte comprising an aluminum salt, a hydrogen-bonding ligand and a diluent.

[0047] The aluminum-based eutectic electrolyte provided by the present invention is a eutectic solvent formed by mixing aluminum salt and hydrogen-bonding ligands, which is in a liquid state at room temperature. The eutectic solvent is entirely composed of ions, which improves the conductivity of the battery. The addition of a diluent reduces the viscosity of the eutectic solvent, improves the fluidity of the aluminum-based eutectic electrolyte, and increases the ion conduction speed; the reduced viscosity also increases the wettability of the eutectic solvent to the diaphragm, reduces the ion transmission path, is conducive to the shuttling of aluminum ions between the positive and negative electrodes, and reduces the interface resistance of the aluminum ion battery. Al in the aluminum-based eutectic electrolyte 3+ The ion concentration is lower than 5 mol / L. The aluminum-based eutectic electrolyte provided by the present invention is not easy to react with common metals and has low corrosiveness, thereby ensuring the service life and safety of the battery.

[0048] Eutectic solvents have similar properties to ionic liquids. They are in liquid state at room temperature. They are mainly composed of hydrogen bond donors and hydrogen bond ligands to form binary and ternary eutectic solvents. The most significant physical property of the eutectic solvents is the reduction of the melting point of the solvent. As a new type of green reagent that can replace ionic liquids, it has a wide range of uses. Compared with ionic liquids, the preparation of eutectic solvents is simpler, faster, and less costly, and has lower toxicity. It has developed rapidly in the past five years and its application range is becoming more and more extensive.

[0049] Optionally, Al 3+ Concentration <5mol / L.

[0050] Preferably, the viscosity of the aluminum-based eutectic electrolyte is lower than 40 mPa / s.

[0051] Optionally, the molar ratio of the aluminum salt to the hydrogen bonding ligand is 1:1-15.

[0052] When the molar ratio of aluminum salt to hydrogen-bonding ligand is less than 1:15, the prepared solution will show stratification and phase separation and cannot form a eutectic electrolyte.

[0053] In some embodiments of the invention, the molar ratio of the aluminum salt to the hydrogen bonding ligand is typically but not limited to 1:1, 1:3, 1:5, 1:7, 1:9, 1:11, 1:13 or 1:15.

[0054] Preferably, the volume ratio of the total volume of the aluminum salt and the hydrogen bonding ligand to the volume of the diluent is 1:0.5-5.

[0055] When the volume ratio of the total volume of aluminum salt and hydrogen bonding ligands to the volume ratio of the diluent is greater than 1:0.5, the effects of reducing the viscosity of the eutectic electrolyte and improving the conductivity are not obvious; when the volume ratio of the total volume of aluminum salt and hydrogen bonding ligands to the volume ratio of the diluent is less than 1:5, turbidity and stratification of the electrolyte are likely to occur.

[0056] In some embodiments of the present invention, the volume ratio of the total volume of the aluminum salt and the hydrogen bonding ligand to the volume of the diluent is typically but not limited to 1:0.5, 1:1, 1:2, 1:3, 1:4 or 1:5.

[0057] Optionally, the aluminum salt includes at least one of aluminum chloride, aluminum chloride hexahydrate, aluminum trifluoromethanesulfonate, aluminum nitrate, aluminum nitrate nonahydrate, aluminum perchlorate, aluminum perchlorate nonahydrate, aluminum sulfate and aluminum sulfate 18hydrate.

[0058] Optionally, the hydrogen bonding ligand includes at least one of sulfone compounds, alcohol compounds, urea and its derivatives, piperidine compounds, nitrile compounds and amide compounds.

[0059] Preferably, the sulfone compound includes dimethyl sulfoxide and / or sulfolane.

[0060] Preferably, the alcohol compound includes at least one of ethylene glycol, polyethylene glycol-200, polyethylene glycol-400 and polyethylene glycol-600.

[0061] Preferably, the urea and its derivatives include at least one of urea, N-methylurea and ethylurea.

[0062] Preferably, the piperidine compound comprises tetramethylpiperidinyl oxide and / or 4-methoxy-tetramethylpiperidinyl oxide free radical.

[0063] Preferably, the nitrile compound comprises succinonitrile and / or acetonitrile.

[0064] Preferably, the amide compound includes at least one of thioacetamide, methylamide and acetamide.

[0065] Optionally, the diluent comprises a hydrofluoroether compound.

[0066] Preferably, the hydrofluoroether compound includes at least one of 2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl ethyl ether, 1,1,2,2-tetrafluoroethyl methyl ether and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

[0067] The second aspect of the present invention provides a method for preparing the aluminum-based eutectic electrolyte, wherein the aluminum salt and the hydrogen-bonding ligand are mixed evenly, heated and then cooled, and a diluent is added and mixed evenly to obtain the aluminum-based eutectic electrolyte.

[0068] The method for preparing the aluminum-based eutectic electrolyte provided by the present invention has a simple process and a large processing capacity and is suitable for large-scale industrial production.

[0069] Optionally, the heating temperature is 40°C-60°C.

[0070] Aluminum salt and hydrogen bonding ligand can form a eutectic solvent at 40°C-60°C. In some embodiments of the present invention, the heating temperature is typically but not limited to 40°C, 45°C, 50°C, 55°C or 60°C.

[0071] Preferably, the heating time is 30 min-60 min.

[0072] Preferably, the method further comprises a stirring process after heating and cooling, and the stirring time is preferably 1 h to 6 h.

[0073] A third aspect of the present invention provides a secondary aluminum ion battery, comprising a positive electrode material, a negative electrode material and an electrolyte solution;

[0074] Wherein, the electrolyte solution is the aluminum-based eutectic electrolyte.

[0075] The secondary aluminum ion battery provided by the present invention uses an aluminum-based eutectic electrolyte, so that the reversible discharge capacity of the battery can reach 300 mAh g -1 The secondary aluminum ion battery has high specific capacity, good cycle stability, higher safety, and is suitable for large-scale promotion and use.

[0076] Optionally, the positive electrode material is Al 3+ Storage material, the negative electrode material is aluminum foil.

[0077] In some embodiments of the present invention, the Al 3+ The storage material includes at least one of vanadium pentoxide, manganese dioxide, molybdenum disulfide, polyaniline, Prussian blue and graphite.

[0078] In some embodiments of the present invention, the aluminum foil includes pure aluminum foil and / or Al—Mg—Sn alloy foil.

[0079] In some embodiments of the present invention, the thickness of the aluminum foil is 1 μm-300 μm.

[0080] The present invention is further described below by specific examples and comparative examples, but it should be understood that these examples are only used for more detailed description and should not be understood as limiting the present invention in any form. The raw materials used in the examples and comparative examples of the present invention, if no specific conditions are specified, are carried out according to conventional conditions or conditions recommended by the manufacturer. The reagents or instruments used without indicating the manufacturer are all conventional products that can be purchased commercially.

[0081] Example 1

[0082] This embodiment provides an aluminum-based eutectic electrolyte, and the specific process is as follows: aluminum chloride and hydrogen bonding ligand dimethyl sulfoxide are mixed in a molar ratio of 1:1, heated at 60°C for 60 minutes until the system presents a uniform liquid state, then naturally cooled to room temperature, and stirred for 3 hours to obtain a corresponding eutectic solvent. Subsequently, the eutectic solvent and the diluent 2,2,2-trifluoroethyl ether are uniformly mixed in a volume ratio of 1:0.5, and a clear and transparent aluminum-based eutectic electrolyte is prepared after stirring for 6 hours.

[0083] The prepared aluminum-based eutectic electrolyte is used as the electrolyte of an aluminum ion battery, a pure aluminum foil (thickness 100 microns) is used as a negative electrode, and vanadium pentoxide is used as a positive electrode to assemble an aluminum ion battery.

[0084] Example 2

[0085] This embodiment provides an aluminum-based eutectic electrolyte, and the specific process is as follows: aluminum chloride hexahydrate and hydrogen bonding ligand ethylene glycol are mixed in a molar ratio of 1:3, heated at 50°C for 40 minutes until the system presents a uniform liquid state, then naturally cooled to room temperature, and stirred for 1 hour to obtain a corresponding eutectic solvent. Subsequently, the eutectic solvent and the diluent 1,1,2,2-tetrafluoroethyl ethyl ether are uniformly mixed in a volume ratio of 1:2, and a clear and transparent aluminum-based eutectic electrolyte is prepared after stirring for 3 hours.

[0086] The prepared aluminum-based eutectic electrolyte is used as the electrolyte of an aluminum ion battery, an aluminum alloy foil is used as a negative electrode (thickness 10 microns), and manganese dioxide is used as a positive electrode to assemble an aluminum ion battery.

[0087] Example 3

[0088] This embodiment provides an aluminum-based eutectic electrolyte, and the specific process is as follows: aluminum trifluoromethanesulfonate and hydrogen-bonding ligand tetramethylpiperidinoxide are mixed in a molar ratio of 1:8, heated at 30°C for 60 minutes until the system presents a uniform liquid state, then naturally cooled to room temperature, and stirred for 3 hours to obtain a corresponding eutectic solvent. Subsequently, the eutectic solvent and the diluent 2,2,2-trifluoroethyl ether are uniformly mixed in a volume ratio of 1:3, and stirred for 6 hours to prepare a clear and transparent aluminum-based eutectic electrolyte.

[0089] The prepared aluminum-based eutectic electrolyte is used as the electrolyte of an aluminum ion battery, a pure aluminum foil (300 microns thick) is used as the negative electrode, and molybdenum disulfide is used as the positive electrode to assemble an aluminum ion battery.

[0090] Example 4

[0091] This embodiment provides an aluminum-based eutectic electrolyte, and the specific process is as follows: aluminum nitrate and hydrogen bonding ligand succinonitrile are mixed in a molar ratio of 1:12, heated at 40°C for 30 minutes until the system presents a uniform liquid state, then naturally cooled to room temperature, and stirred for 3 hours to obtain a corresponding eutectic solvent. Subsequently, the eutectic solvent and the diluent 1,1,2,2-tetrafluoroethyl methyl ether are uniformly mixed in a volume ratio of 1:4, and a clear and transparent aluminum-based eutectic electrolyte is prepared after stirring for 6 hours.

[0092] The prepared aluminum-based eutectic electrolyte is used as the electrolyte of an aluminum ion battery, a pure aluminum foil (50 microns thick) is used as the negative electrode, and polyaniline is used as the positive electrode to assemble the aluminum ion battery.

[0093] Example 5

[0094] This embodiment provides an aluminum-based eutectic electrolyte, and the specific process is as follows: aluminum nitrate nonahydrate and hydrogen bonding ligand acetonitrile are mixed in a molar ratio of 1:15, heated at 60°C for 35 minutes until the system presents a uniform liquid state, then naturally cooled to room temperature, and stirred for 3 hours to obtain a corresponding eutectic solvent. Subsequently, the eutectic solvent and the diluent 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether are uniformly mixed in a volume ratio of 1:5, and a clear and transparent aluminum-based eutectic electrolyte is prepared after stirring for 6 hours.

[0095] The prepared aluminum-based eutectic electrolyte was used as the electrolyte of an aluminum ion battery, an aluminum alloy foil (thickness 20 microns) was used as the negative electrode, and Prussian blue was used as the positive electrode to assemble the aluminum ion battery.

[0096] Example 6

[0097] This embodiment provides an aluminum-based eutectic electrolyte, and the specific process is as follows: aluminum perchlorate, aluminum sulfate and hydrogen-bonding ligand thioacetamide are mixed in a molar ratio of 1:1:10, heated at 60°C for 20 minutes until the system presents a uniform liquid state, then naturally cooled to room temperature, and stirred for 4 hours to obtain a corresponding eutectic solvent. Subsequently, the eutectic solvent and the diluent 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether are uniformly mixed in a volume ratio of 1:4, and a clear and transparent aluminum-based eutectic electrolyte is prepared after stirring for 6 hours.

[0098] The prepared aluminum-based eutectic electrolyte is used as the electrolyte of an aluminum ion battery, an aluminum alloy foil (thickness 40 microns) is used as the negative electrode, and graphite is used as the positive electrode to assemble the aluminum ion battery.

[0099] Example 7

[0100] This embodiment provides an aluminum-based eutectic electrolyte, and the specific process is as follows: aluminum sulfate 18hydrate, aluminum perchlorate nonahydrate and hydrogen-bonding ligand tetramethylpiperidinoxide are mixed in a molar ratio of 1:1:8, heated at 40°C for 60 minutes until the system presents a uniform liquid state, then naturally cooled to room temperature, and stirred for 3 hours to obtain the corresponding eutectic solvent. Subsequently, the eutectic solvent and the diluent 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether are uniformly mixed in a volume ratio of 1:2, and a clear and transparent aluminum-based eutectic electrolyte is prepared after stirring for 6 hours.

[0101] The prepared aluminum-based eutectic electrolyte is used as the electrolyte of an aluminum ion battery, an aluminum alloy foil (5 microns in thickness) is used as a negative electrode, and polyaniline is used as a positive electrode to assemble an aluminum ion battery.

[0102] Comparative Example 1

[0103] This comparative example provides an aluminum-based eutectic electrolyte. Unlike Example 3, no diluent 2,2,2-trifluoroethyl ether is added. The remaining methods and steps are the same as those in Example 3 and will not be repeated here.

[0104] Comparative Example 2

[0105] This comparative example provides an aluminum ion battery. The difference from Example 3 is that the electrolyte is 1-ethyl-3-methylimidazolium chloroaluminate (AlCl3 / [EMIm]Cl) ionic liquid, and the specification is that the molar ratio of anhydrous AlCl3:[EMIm]Cl is 1.3:1. The remaining methods and steps are the same as those in Example 3 and will not be repeated here.

[0106] Test Example 1

[0107] The aluminum-based eutectic electrolyte obtained in Examples 1-7 was tested for aluminum ion concentration and viscosity. The test results are as follows: Figure 1 shown.

[0108] Test Example 2

[0109] The aluminum ion batteries obtained in Examples 1-7 and Comparative Examples 1-2 were subjected to charge and discharge capacity tests.

[0110] The test process is as follows: the charge and discharge voltage range is 0.4V-1.6V, and the current density is 100mA / g.

[0111] Table 1 Reversible discharge capacity data table

[0112] <![CDATA[Reversible discharge capacity (mAh·g -1 )]]> Example 1 249 Example 2 256 Example 3 300 Example 4 242 Example 5 152 Example 6 221 Example 7 240 Comparative Example 1 198 Comparative Example 2 223

[0113] As can be seen from Table 1, the positive electrode materials of Example 3 and Example 5 are different, so the capacities are different. The ionic conductivity of the eutectic electrolyte is directly related to the capacity of the battery. The eutectic electrolyte after adding the diluent has a significant improvement in the battery capacity, which is due to the improvement in the ionic conductivity of the electrolyte. In addition, the eutectic electrolyte has good compatibility with a variety of positive electrode materials, and the full battery has excellent capacity performance.

[0114] Test Example 3

[0115] The aluminum ion batteries obtained in Examples 1-7 were subjected to charge and discharge capacity tests and cycled 5 times to obtain the following results: Figure 2-Figure 8 , Figure 2-Figure 8 The charge and discharge curves of the aluminum ion batteries provided in Examples 1 to 7 are shown in Table 1. Figure 2-Figure 8 It can be seen that the whole battery based on the eutectic electrolyte after diluent shows a high discharge capacity as a whole. This is due to the fact that the diluent reduces the viscosity of the electrolyte and improves the ionic conductivity of the electrolyte without affecting the original electrolyte solvation structure. In addition, the high coulombic efficiency performance indicates that after the diluent is added, there are fewer side reactions, which improves the cycle stability of the whole battery.

[0116] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or replace some or all of the technical features therein with equivalents. However, these modifications or replacements do not cause the essence of the corresponding technical solutions to deviate from the scope of the technical solutions of the embodiments of the present invention.

Claims

1. An aluminum-based eutectic electrolyte, characterized in that: including aluminum salts, hydrogen bonding ligands, and diluents; The molar ratio of the aluminum salt to the hydrogen bonding ligand is 1:1-15; the volume ratio of the total volume of the aluminum salt and the hydrogen bonding ligand to the diluent is 1:0.5-5; The aluminum salt includes at least one of aluminum chloride, aluminum chloride hexahydrate, aluminum trifluoromethanesulfonate, aluminum nitrate, aluminum nitrate nonahydrate, aluminum perchlorate, aluminum perchlorate nonahydrate, aluminum sulfate, and aluminum sulfate 18hydrate; The hydrogen bonding ligand includes at least one of sulfone compounds, alcohol compounds, urea and its derivatives, piperidine compounds, nitrile compounds and amide compounds; The sulfone compound includes dimethyl sulfoxide and / or sulfolane; The alcohol compound includes at least one of ethylene glycol, polyethylene glycol-200, polyethylene glycol-400 and polyethylene glycol-600; The urea and its derivatives include at least one of urea, N-methylurea and ethylurea; The piperidine compound includes tetramethyl piperidine oxide and / or 4-methoxy-tetramethyl piperidine oxide free radical; The nitrile compound includes succinonitrile and / or acetonitrile; The amide compound includes at least one of thioacetamide, methylamide and acetamide; The diluent includes a hydrofluoroether compound; The hydrofluoroether compound includes at least one of 2,2,2-trifluoroethyl ether, 1,1,2,2-tetrafluoroethyl ethyl ether, 1,1,2,2-tetrafluoroethyl methyl ether and 1,1,2,2-tetrafluoroethyl-2,2,3,3-tetrafluoropropyl ether.

2. The aluminum-based eutectic electrolyte according to claim 1, characterized in that Al 3+ Concentration <5 mol / L.

3. The aluminum-based eutectic electrolyte according to claim 1, characterized in that The viscosity of the aluminum-based eutectic electrolyte is lower than 40 mPa / s.

4. A method for preparing the aluminum-based eutectic electrolyte according to any one of claims 1 to 3, characterized in that: The aluminum salt and the hydrogen-bonding ligand are mixed evenly, heated, and then cooled, and a diluent is added and mixed evenly to obtain the aluminum-based eutectic electrolyte.

5. The preparation method according to claim 4, characterized in that: The heating temperature is 40°C-60°C.

6. The preparation method according to claim 4, characterized in that: The heating time is 30min-60min.

7. The preparation method according to claim 4, characterized in that: It also includes a stirring process after heating and cooling, and the stirring time is 1h-6h.

8. A secondary aluminum ion battery, characterized in that: including positive electrode material, negative electrode material and electrolyte solution; Wherein, the electrolyte solution is the aluminum-based eutectic electrolyte described in any one of claims 1-3 or the aluminum-based eutectic electrolyte prepared by the preparation method described in any one of claims 4-7.

9. The secondary aluminum ion battery according to claim 8, characterized in that: The positive electrode material is Al 3+ Storage material, the negative electrode material is aluminum foil.

10. The secondary aluminum ion battery according to claim 9, characterized in that: The Al 3+ The storage material includes at least one of vanadium pentoxide, manganese dioxide, molybdenum disulfide, polyaniline, Prussian blue and graphite.

11. The secondary aluminum ion battery according to claim 9, characterized in that: The aluminum foil includes pure aluminum foil and / or Al-Mg-Sn alloy foil.

12. The secondary aluminum ion battery according to claim 9, characterized in that: The thickness of the aluminum foil is 1 μm-300 μm.

Citation Information

Patent Citations

  • Eutectic solvent electrolyte solution, preparation method thereof and aluminum ion secondary battery

    CN114784384A